blakemancillas
\((\sqrt{9+\sqrt{80}}+\sqrt{9-\sqrt{80}})^2=\)
A. 1
B. 9 - 4*5^1/2
C. 18 - 4*5^1/2
D. 18
E. 20
\(A = \sqrt {9 + \sqrt {80} }\)
\(B = \sqrt {9 - \sqrt {80} }\)
\(?\,\,\,:\,\,\,{\text{expression}}\,\,{\text{ = }}\,\,{\left( {A + B} \right)^{\text{2}}}{\text{ = }}{{\text{A}}^{\text{2}}} + 2AB + {B^2}\)
\({A^2} = {\left( {\sqrt {9 + \sqrt {80} } } \right)^2} = 9 + \sqrt {80}\)
\({B^2} = {\left( {\sqrt {9 - \sqrt {80} } } \right)^2} = 9 - \sqrt {80}\)
\(AB = \sqrt {9 + \sqrt {80} } \cdot \sqrt {9 - \sqrt {80} } = \sqrt {\left( {9 + \sqrt {80} } \right)\left( {9 - \sqrt {80} } \right)} \,\,\,\mathop = \limits^{\left( * \right)} \,\,\,\sqrt 1 = \boxed1\)
\(\left( * \right)\,\,\,\,\,\left( {9 + \sqrt {80} } \right)\left( {9 - \sqrt {80} } \right)\,\,\, = \,\,\,\,{9^2} - {\left( {\sqrt {80} } \right)^2} = 81 - 80 = 1\)
\(? = \left( {9 + \sqrt {80} } \right) + 2 \cdot \boxed1 + \left( {9 - \sqrt {80} } \right) = 20\)
This solution follows the notations and rationale taught in the GMATH method.
Regards,
fskilnik.